Evaluating Capital Market Education to Enhance Investment Interest and Financial Inclusion: A Mixed Methods Aproach - Ramdani, Muhammad; Pratiwi, Septiana Eka; Hairullah, Muhammad Tezar; Cahaya, Tita Putri; Nurfadliyah, Nurfadliyah (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2024)
The year 2020 witnessed a resurgence of domestic retail investors in the Indonesian Capital Market, fueled by the COVID-19 pandemic. The national trend in stock investor growth shows a significant increase, whereas at Investment Gallery at the University of Technology Sumbawa, there has been a declining trend in percentage terms. The prevalence of fraudulent investment schemes, such as the Financial FEC, claiming 80,000 victims, underscores the pivotal role of the Investment Gallery at the University of Technology Sumbawa in the Sumbawa Regency The research aims to: 1) Identify the characteristics of the Investment Gallery of the University of Technology Sumbawa education participants, capital market education, investment knowledge, investment interest, and financial inclusion. 2) Analyze the impact of capital market education and investment knowledge, mediated by investment interest, on the financial inclusion of the Investment Gallery of the University of Technology Sumbawa education participants. 3) Explore the strategies and methods used in education by Investment Gallery of the University of Technology Sumbawa. This research utilizes a mixed-method approach, with primary data collected through questionnaires from 100 respondents and in-depth interviews with 6 selected respondents and Investment Gallery at the University of Technology Sumbawa stakeholders, along with secondary data from Investment Gallery at the University of Technology Sumbawa and other sources. The research findings indicate that the levels of capital market education, investment knowledge, investment interest, and financial inclusion are at a moderate level. The results of the Structural Equation Modeling (SEM) indicate that capital market education and investment knowledge do not have a direct or indirect influence on financial inclusion through investment interest. Furthermore, the efforts in capital market education by Investment Gallery at the University of Technology Sumbawa are not yet optimal, the use of social media for education is underutilized, and collaboration with government and campus and non-campus organizations has not been established.